A Prospective Study on Tracking and Reporting of Adverse Medication Responses in Patients Referred to a Teaching Hospital for Tertiary Care - Khatawakar, Aishwarya Laxmikant; Gudi, Josthna Raghunath; Kora, Shreeram; Patil, Madhu; Morabad, Soumya; V.M, Chandrashekhar (Indian Journal of Pharmacy Practice)
Adverse medication responses are one of the major factors contributing to morbidity and mortality. Every time a patient is exposed to a medicinal product, it's a special circumstance, and there's no way to predict what might happen. Aim was to identify and report adverse medication responses. This prospective, observational, spontaneous reporting study was carried out at HSK Hospital in Bagalkot, Karnataka, India, over the course of six months. During the course of the trial, 114 patients reported a total of 154 ADRs. Male patients (54.54%) reported a greater percentage of adverse drug reactions than female patients (45.46%). The most frequently encountered ADRs in the study population were hypotension, nephrotoxicity, constipation, and loose stools. Antihypertensive (20.7%), Anti-TB (17.5%), and Antibiotic (14.93%) medication classes caused more Adverse Drug Reactions (ADRs) than others. The organ system mostly affected by Adverse medication responses was the Gastrointestinal system (17.53%), followed by the Endocrine system (16.23%), Dermatology (14.28%). By this, we conclude that regularly tracking and reporting adverse medication responses can reveal information about their efficacy and pattern of occurrence. Similar reporting initiatives are required to inform and raise awareness about the reporting of ADRs among hospital medical staff. Studies of this nature that report Adverse medication responses will aid in promoting the safety of medication therapy.
Keywords: Adverse medication responses; Pharmacovigilance; Safety of medication therapy